(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Infertility is a pressing issue that negatively impacts reproductive health and the overall quality of life of women. According to the World Health Organization (WHO), 15-20% of women of reproductive age face infertility issues.To identify the main causes of infertility in women with a “thin” endometrium through modern olved 80 women with primary and secondary infertility due to endometrial hypoplasia. All women were between 22 and 35 years old and were divided into two groups:Group I: 40 infertile women who received only antiplatelet therapy.Group II: 40 women who received a combination of PRP therapy and antiplatelet treatment.The study utilized general clinical, gynecological examination, ultrasound (USG) and Doppler imaging, hormonal, biochemical, morphological, and statistical methods.Results. In Group II, where PRP therapy was combined with antiplatelet agents, successful pregnancy outcomes were achieved in 33 out of 40 women (82.5%), while in Group I, the success rate was 20 out of 40 (50%).